Stereotaxic use of the 980 nm diode laser in rat cortical and subcortical tissues - (:unkn) unknown (My University, 2001)
The use of 980 nm diode laser irradiation within cortical tissue was investigated by the authors' previous work. In the present study (a) the lesions created in cortical and subcortical tissues and (b) lesioning effects of diode laser applied in continuous and pulsed regimes were compared. In vivo stereotaxic neurosurgical procedure was performed on female Wistar rats' cortical and subcortical tissues. 980 nm diode laser was applied in two different regimes, cw and pulsed wave respectively. Lesion dimensions were measured and compared. The lasing parameters were found suitable for both brain regions. No significant difference was found between tissues. Lesion diameters varied in the range of 1.0-9.0 mm. Histological examination revealed data for a limited thermal damage in the surrounding tissue for all lesions. Cortical and subcortical tissues did not show significant differences due to same amount of energy delivered. The lasing regime did not influence the dimensions of lesions. Applied energy was found the key element determining the amount of lesion. Results were consistent with the findings found in the previous dosimetry studies.
Keywords: 980 nm diode laser; Brain; Coagulation; Rat; Stereotaxic neurosurgery